Omnibus Method in National Legal Development Efforts - Putri Aji, Rizka Ananda; Susilawati, Elis (Universitas Islam Negeri Raden Fatah Palembang, 2023)
Pancasila is the view of life of the nation and state which is the basis for the implementation of national life. The precepts in